2017
DOI: 10.1684/epd.2017.0901
|View full text |Cite
|
Sign up to set email alerts
|

Epileptic spasms in congenital disorders of glycosylation

Abstract: Aim. Congenital disorders of glycosylation (CDG) are a group of rare metabolic diseases, characterized by impaired glycosylation. Multisystemic involvement is common and neurological impairment is notably severe and disabling, concerning the central and peripheral nervous system. Epilepsy is frequent, but detailed electroclinical description is rare. Methods. We describe, retrospectively, the electroclinical features in five children with CDG and epileptic spasms. Results. Epileptic spasms were observed in pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…ISs have been also reported in children with neurodegenerative disorders including globoid cell leukodystrophy-Krabbe disease (caused by the GALC gene) and Menkes disease (caused by the ATP7A gene) [58][59][60]. Rare disorders associated with ISs also include cerebrotendineous xantomatosis (caused by the CYP27A1 gene) [61]; glucose transport 1 deficiency (caused by mutations in exon 9 of the SLC2A1 gene) [62]; disorders of glycosylation [63] (caused by the ALG1,6,11 genes: subtypes CDG and CDG 1x). Pyridoxine-dependent epilepsy (PDE) may present with various types of severe seizures, partial and generalized seizures, atonic and myoclonic seizures, convulsive status epilepticus, and ISs [64,65].…”
Section: Inborn Errors Of Metabolismmentioning
confidence: 99%
“…ISs have been also reported in children with neurodegenerative disorders including globoid cell leukodystrophy-Krabbe disease (caused by the GALC gene) and Menkes disease (caused by the ATP7A gene) [58][59][60]. Rare disorders associated with ISs also include cerebrotendineous xantomatosis (caused by the CYP27A1 gene) [61]; glucose transport 1 deficiency (caused by mutations in exon 9 of the SLC2A1 gene) [62]; disorders of glycosylation [63] (caused by the ALG1,6,11 genes: subtypes CDG and CDG 1x). Pyridoxine-dependent epilepsy (PDE) may present with various types of severe seizures, partial and generalized seizures, atonic and myoclonic seizures, convulsive status epilepticus, and ISs [64,65].…”
Section: Inborn Errors Of Metabolismmentioning
confidence: 99%
“…All the previously reported ALG11‐CDG patients have epilepsy. A recent paper by Pereira (Pereira et al, ) describes that CDG can be associated with epileptic seizures showing particular features, such as absence of hypsarrhythmia, posterior EEG anomalies, and an unusual combination of epileptic seizures with myoclonus. Their patient with ALG11‐CDG presented with typical epileptic seizures that were either in very long‐lasting clusters or isolated, but also had focal clonic seizures and rare isolated massive jerks with a combination of myoclonus and spasm.…”
Section: Discussionmentioning
confidence: 99%
“…To date, only 10 patients have been described with ALG11‐CDG (OMIM# 613661) (Al Teneiji et al, ; Pereira et al, ; Regal et al, ; Rind et al, ; Thiel et al, ). We report two additional unrelated patients to expand the ALG11‐CDG phenotype to include normal transferrin glycosylation as determined by mass spectrometry in one individual, together with functional studies supporting the pathogenicity of their novel ALG11 mutations.…”
Section: Introductionmentioning
confidence: 99%
“…Pereira et al reported a case of ALG6-CDG with epileptic spasms and generalized tonic-clonic seizures (onset at age 6 months) without hypsarrhythmia (but with abundant posterior interictal spikes and sharp waves). 13 …”
Section: Discussionmentioning
confidence: 99%
“…Pereira et al reported a case of ALG6-CDG with epileptic spasms and generalized tonic-clonic seizures (onset at age 6 months) without hypsarrhythmia (but with abundant posterior interictal spikes and sharp waves). 13 To date, there are less than 100 ALG6-CDG cases reported in the literature. All share the phenotype of hypotonia and developmental delay, and the majority (perhaps >70%) have seizures, 12 but a minority have medically intractable epilepsy.…”
Section: Discussionmentioning
confidence: 99%